Comparison of Physical Fitness and Respiratory Parameters of Elite Wrestlers and Judokas - Ahmet Koyunlu; Önder Dağlıoğlu; Mustafa Özdal (Selcuk University, 2020)
The aim of this study was to comparison of physical fitness and respiratory parameters of wrestlers and judokas. A total of 24 athletes in the 19-21 age range, 12 male wrestlers and 12 male judoists were volunteers. Physical fitness parameters for subjects; age, body weight, height, body mass index (BMI), body fat percentage (BF%), hand grip strength, 20 m sprint tests, maxVO2, vertical jump, as respiratory parameters, forced expiratory volume (FEV1), forced vital capacity (FVC), forced expiration ratio (FEV1/FVC), maximum voluntary volume (MVV) and vital capacity (VC) test measurements were performed. Independent Samples T test was used to analyze the data. In the physical fitness parameters of the groups; Age, body weight, height, BMI, BF%, 20 m sprint test, maxVO2 and vertical jumping values were not significant. The right and left hand grip strength values were found to be significant in favor of wrestlers. FEV1, FVC, FEV1/FVC, MVV and VC values were not significantly different between the groups. As a result; as the technical structure and performance components of wrestling and judo branches show similar characteristics, it can be said that wrestlers and judoists have similar characteristics in terms of physical fitness and respiratory parameters.